STRATEGI PEMASARAN PARIWISATA KABUPATEN JEPARA - Admesia Iyangjaya Peringatan; Reni Windiani; Sulistyowati . (Journal of Politic and Government Studies, 2013)
Tourism is a service industry that is used as one of the drivers of the economy in theworld. Tourism is a rapidly growing industry in the world. In Indonesia, tourism is athird country foreign exchange earner after oil and textiles. Jepara regency has potentialhas yet to be optimized until now, the potential for tourism. Jepara regency is one of thefew areas that have become a tourist attraction and one of the tourist destinations inCentral Java Province. That intersect with the existence of Jepara Java Sea make thisdistrict has a natural charm beautiful beaches. In this regard it is necessary to know thestrategy of Tourism and Culture of Jepara in its efforts to develop the tourism sector ofthe region and know the obstacles of Tourism and Culture of Jepara in improving thetourism sector.Methods This study is a descriptive study with a qualitative design. This studydescribes the tourism marketing strategy in Jepara regency. Many existing attractions